1999
DOI: 10.1126/science.283.5401.543
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Constitutive TNF Receptor 1 Signaling by Silencer of Death Domains

Abstract: Tumor necrosis factor receptor type 1 (TNF-R1) contains a cytoplasmic death domain that is required for the signaling of TNF activities such as apoptosis and nuclear factor kappa B (NF-kappaB) activation. Normally, these signals are generated only after TNF-induced receptor aggregation. However, TNF-R1 self-associates and signals independently of ligand when overexpressed. This apparent paradox may be explained by silencer of death domains (SODD), a widely expressed approximately 60-kilodalton protein that was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
283
3
7

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 371 publications
(301 citation statements)
references
References 17 publications
6
283
3
7
Order By: Relevance
“…Finally, it is possible that intracellular TNFR1 interacts with intracellular proteins different from those identified as interacting with plasma membrane receptor. One such candidate could be SODD (silencer of death domains), which has recently been reported to bind to the intracellular region of TNFR1 in the absence of TNF, thereby preventing receptor self-aggregation and blocking the recruitment of TRADD and down-stream signaling (Jiang et al, 1999). However, in preliminary experiments we did not see co-localization of SODD with TNFR1 in the Golgi (Gaeta ML, unpublished observation).…”
Section: Figurementioning
confidence: 79%
“…Finally, it is possible that intracellular TNFR1 interacts with intracellular proteins different from those identified as interacting with plasma membrane receptor. One such candidate could be SODD (silencer of death domains), which has recently been reported to bind to the intracellular region of TNFR1 in the absence of TNF, thereby preventing receptor self-aggregation and blocking the recruitment of TRADD and down-stream signaling (Jiang et al, 1999). However, in preliminary experiments we did not see co-localization of SODD with TNFR1 in the Golgi (Gaeta ML, unpublished observation).…”
Section: Figurementioning
confidence: 79%
“…41 It has been reported that Hsp70 associated with Bag-4 binds to the death domain of TNFR1 or DR3 and thus prevents self-aggregation to functional trimers initiating caspasedependent apoptotic cell death. 42 Therefore, we hypothesized that membrane-bound Hsp70/Bag-4 might also be linked to the cytosolic domain of TNFR1. However, neither CX þ /CXÀ nor Colo þ /ColoÀ carcinoma sublines exhibited TNFR1 or DR3 on their cell membranes.…”
Section: Discussionmentioning
confidence: 99%
“…This offers new insights into the biological functions of BMPs (Chen et al, 2001). There are proteins that associate with cytokine receptors, such as SODD (for silencer of death domain) (Jiang et al, 1999), sentris (Okura et al, 1996), and c-FLIP (Scaffidi et al, 1999). These can also negatively regulate apoptosis, again independently of NF-κB.…”
Section: Evidence That Apoptosis Is Unaffected By Nf-kappabmentioning
confidence: 99%